Generative Artificial Intelligence and Web Accessibility: Towards an Inclusive and Sustainable Future - Patricia Acosta-Vargas; Belén Salvador-Acosta; Sylvia Novillo-Villegas; Demetrios Sarantis; Luis Salvador-Ullauri (Emerging Science Journal, 2024)
This study examines the accessibility of Generative Artificial Intelligence (AI) tools for people with disabilities, using WCAG 2.2 success criteria as a reference. Significant accessibility issues were identified in the evaluated applications, highlighting barriers mainly affecting disabled users. Integrating accessibility considerations from the beginning of application development and adopting a proactive approach are emphasized. Although challenges are faced, such as the shortage of inclusive training data and opacity in AI decision-making, the need to continue addressing various aspects of accessibility in the field of generative AI tools is acknowledged. These efforts are based on regulatory compliance and ethical principles to ensure equal societal participation, regardless of individual abilities. The fundamental role of accessibility in realizing this vision is highlighted, aligning with the United Nations Sustainable Development Goals, particularly those related to equality, education, innovation, and inclusion. Improving accessibility meets regulatory requirements and contributes to a broader global agenda for a more equitable and sustainable future. Doi: 10.28991/ESJ-2024-08-04-021 Full Text: PDF